Partnerships and Community Building as Collaborative Assistance: Insights on Goal Presence, Hierarchy, and Integration from Urban Park Plans - Elizabeth E. Perry; Ellie A. Schiappa; Allison McCurdy (Urban Science)
Urban parks provide areas for human wellbeing and green space benefits in densely populated landscapes but cannot accomplish all their goals in isolation. They require assistance from collaborations to address challenges. The need for these collaborations is often codified in planning documents. We assisted Rock Creek Park (National Park Service, Washington, D.C.) in their considerations of where to place “partnerships” in their strategic plan by sourcing and summarizing goal topics, hierarchies, and relationships from peer park plans. Using textual coding and network analysis approaches, we examined strategic planning documents from park system entities across the 20 largest urban areas in the United States. We found that, topically, Rock Creek Park’s five initial strategic planning goal topics—safety, access, stewardship, community engagement, and employee engagement—were common and both inward and outward-facing goals. Hierarchically, “partnerships” was routinely considered as a primary goal (a stand-alone topic) and as an integrated secondary goal (supportive within other topics). Additionally, we identified “community building” as an important, outward facing “assistance” goal, differentiated from “partnerships” in audience and encompassing how a park shows up for the urban community and demonstrates its value to the region. We discuss these findings toward urban park planning processes.